2013
DOI: 10.2105/ajph.2012.301009
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting More Than Vegetables: The Potential Weight Control Benefits of Community Gardening

Abstract: Objectives. We examined the association of participation in community gardening with healthy body weight. Methods. We examined body mass index (BMI) data from 198 community gardening participants in Salt Lake City, Utah, in relationship to BMI data for 3 comparison groups: neighbors, siblings, and spouses. In comparisons, we adjusted for gender, age, and the year of the BMI measurement. Results. Both women and men community gardeners had significantly lower BMIs than did their neighbors who were not in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 30 publications
7
117
1
10
Order By: Relevance
“…Gardening has been associated with a healthier diet and lower BMIs (Alaimo et al 2008;Litt et al 2011;van den Berg et al 2010;Wakefield et al 2007;Zick et al 2013). Although participants in our study were overweight, the majority reported good to excellent health.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 57%
See 1 more Smart Citation
“…Gardening has been associated with a healthier diet and lower BMIs (Alaimo et al 2008;Litt et al 2011;van den Berg et al 2010;Wakefield et al 2007;Zick et al 2013). Although participants in our study were overweight, the majority reported good to excellent health.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 57%
“…Similarly, other studies have shown that community gardens provide a space and activity around which to socialize and develop social networks (Carney et al 2012;Harris et al 2014;Pitt 2014;Zick et al 2013). …”
Section: Susan Algertmentioning
confidence: 88%
“…A third study (25) observed a relationship of quality (but not quantity) of streetscape greenery with "green" activity, though not with total physical activity. Finally, recent results suggest that community gardening is associated with a lower body mass index (141).…”
Section: Physical Activitymentioning
confidence: 95%
“…Some home food gardeners may view their time and money as worthwhile resources to spend in exchange for engaging in other sustainable behaviors, such as composting their food and garden wastes or caring for the environment by growing food organically. Of course, there are also the well-documented social, mental, health, and education benefits associated with engaging in and practicing UA [55][56][57][58][59][60].…”
Section: Implications For Economic Sustainability Of Home Food Gardensmentioning
confidence: 99%